Setting the international research agenda for sarcoma together with patients and carers: first results of the Sarcoma Patient EuroNet (SPAEN) priority setting partnership - Husson, Olga; Drabbe, C.; Schuster, K.; van Kampen, P.; Koops, C.; Weidema, M.; Davidson, R.; Wartenberg, M.; Artzner, E.; Gonzato, O.; Fernandez, N.; Kasper, Bernd; et al. (ESMO open, 2022)
Background - Research in sarcomas has historically been the domain of scientists and clinicians attempting to understand the disease to develop effective treatments. This traditional approach of placing scientific rigor before the patient’s reality is changing. This evolution is reflected in the growth of patient-centered organizations and patient advocacy groups that seek to meaningfully integrate patients into the research process. The aims of this study are to identify the unanswered questions regarding sarcomas (including gastrointestinal stromal tumors and desmoid fibromatosis) from patient, carer, and clinical perspectives and examine how patients and carers want to be involved in sarcoma research. - Methods - The Patient-Powered Research Network of Sarcoma Patients EuroNet set up a Priority Setting Partnership (PSP) in collaboration with stakeholders from the sarcoma research field. This PSP is largely based on the James Lind Alliance methodology. - Results - In total, 264 sarcoma patients (73%) and carers (27%) from all over the world participated in the online survey and covered the full spectrum of sarcomas. The topics mentioned were labeled in accordance with the Common Scientific Outline of the International Cancer Research Partnership and lists for potential research topics, advocacy topics, and requests for information were constructed. With regard to patient and carer involvement, 64% were very willing to be actively involved and mainly in the following areas: sharing perspectives, discussing patient-clinician interactions, and attending research meetings. - Conclusions - The first results of this sarcoma PSP identified important research questions, but also important topics for patient advocacy groups and further improvement of information materials. Sarcoma patients and carers have a strong wish to be involved in multiple aspects of sarcoma research. The next phase will identify the top 10 research priorities per tumor type. These priorities will provide guidance for research that will achieve greatest value and impact.